2022
DOI: 10.1021/acsanm.1c03323
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fabrication of Lead-Free Cs3Cu2I5 Nanostructures Embedded in Poly(Vinylidene Fluoride) Electrospun Fibers for Polarized Emission

Abstract: Polarized emissive materials with anisotropic nanostructures have attracted tremendous attention as potential substitutes for polarizers. Herein, the electrospinning technique is adopted to realize in situ fabrication of lead-free halide Cs 3 Cu 2 I 5 nanostructures embedded in poly(vinylidene fluoride) (PVDF) micro/ nanofiber films for polarized luminescence generation, with a photoluminescence quantum yield (PLQY) of 33.3−86.1%. The functionality of the polymer PVDF as a protector and its interactions with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…To date, different synthetic approaches have been developed to prepare Cs–Cu–I perovskites, such as colloidal chemical methods, antisolvent strategy, and mechanical grinding methods . The rapid progress made in the synthesis of Cs–Cu–I perovskites drove the development of their applications in light-emitting diodes, photodetectors, anticounterfeiting, and so on. For example, researchers demonstrated that the reversible conversion between blue-emitting Cs 3 Cu 2 I 5 and yellow-emitting CsCu 2 I 3 through exposing or removing water exhibited excellent stability in the anticounterfeiting applications. , Yet, to date, few works have been reported on the relationship between luminescence tuning and phase transition of Cs–Cu–I perovskites on the nanoscale.…”
mentioning
confidence: 99%
“…To date, different synthetic approaches have been developed to prepare Cs–Cu–I perovskites, such as colloidal chemical methods, antisolvent strategy, and mechanical grinding methods . The rapid progress made in the synthesis of Cs–Cu–I perovskites drove the development of their applications in light-emitting diodes, photodetectors, anticounterfeiting, and so on. For example, researchers demonstrated that the reversible conversion between blue-emitting Cs 3 Cu 2 I 5 and yellow-emitting CsCu 2 I 3 through exposing or removing water exhibited excellent stability in the anticounterfeiting applications. , Yet, to date, few works have been reported on the relationship between luminescence tuning and phase transition of Cs–Cu–I perovskites on the nanoscale.…”
mentioning
confidence: 99%
“…Numerous medicated nanoparticles have found their potential applications in drug delivery, while electrospinning has wide application prospects in the field of transdermal drug delivery. Electrospinning is able to treat many kinds of fluids, including solutions, , emulsions, , and nano-suspensions, , and in several manners such as blending, , coaxial, and multiple fluid . Drug-loaded electrospun nanofiber membranes have large specific surface areas, high porosity, and high fluid absorption, which induce a humid environment on the skin cuticle, allowing the fiber membrane to closely fit to the skin, thereby helping drugs enter systemic circulation in the way of dissimilar diffusion along a concentration gradient. Polyacrylonitrile (PAN) is widely used for electrospinning because of its good electrospinnability and stability .…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are suggested for improving the stability of perovskite materials through polymer coating with waterproof materials 19 or encapsulation within a polymer matrix. 20,24 without organic surfactants via electrospinning of a PS and CsI/CuI precursor solution. The perovskites within PS provide uniform yellow and blue emission with a wide full width at half-maximum (FWHM).…”
Section: Introductionmentioning
confidence: 99%
“…Cesium copper halide perovskites (Cs–Cu–X) are representative light-emitting materials that are low-cost and earth-abundant, and provide eco-friendly broad-band emission. The synthesis of Cs–Cu–X compounds has been accomplished using solvent evaporation, mechanochemical reactions, , QDs in surfactants, , melt growth, and vapor codeposition, , which could be used in optoelectronic applications such as anticounterfeiting, , polarization, and white light-emitting devices (WLEDs). , Despite the various advantages and applications mentioned above, Cs 3 Cu 2 I 5 perovskite has low stability in moisture, causing transformation into CsCu 2 I 3 and weak photoluminescence (PL) intensity. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation